ANALISIS DETERMINAN YANG MEMPENGARUHI DIVIDEND PAYOUT RATIO PADA PERUSAHAAN INFRASTRUKTUR DI BEI - Adjie, Jessica Kunta; Lukman, Hendro; Simina, Juni (Jurnal Paradigma Akuntansi, 2024)
This Reseacrh aims to obtain empirical evidence of the effect investment Opportunity Set, Business Risk,Managerial Ownership,Institusional Ownership on Dividend Payout Ratio In Infrastructure companies listed on the Indonesia Stock Exchange for the 2016-2020 period . The sample obtained was based on Purposive Sampling method and the final data used in this study amounted 11 infrastructure companies. The data processing technique use IBM SPSS Version 25 software. The result show the variabel Investment Opportunity Set, Managerial Ownership, Institusional Ownership have no significant and negative effect on dividend payout ratio and the business risk variable has a significant positive effect on dividend payout ratio.